The microbiological-clinical turnover during orthodontic treatment - Aurora Pasqualini; Chiara Fabroni; Matteo Saccucci; Elisabetta Vacros; Lorenza Putignani; Gabriele Di Carlo (Annali di Stomatologia)
Aim: This umbrella review aims to identify the level of evidence regarding the microbiological changes occurring in the oral cavity, with particular attention to changes in the oral microbiota and periodontal indices, in subjects undergoing orthodontic therapy. Methods: The methodology is based on the PICO search criteria within a systematic review and meta-analysis performed on patients undergoing orthodontic treatment with fixed multibracket therapy or aligners. The eligibility of the studies selected was independently assessed. The included reviews were assessed using the Assessing the Methodological Quality of Systematic Reviews (AMSTAR 2) tool, which consists of 16 items. Results: An electronic search database yielded a total of 457 results from 2000 onwards. Of these, 450 titles were discarded as clearly not relevant, while 7 abstracts were selected for further screening. One included review was classified as grey literature. In total, 8 studies were included in this review of systematic reviews. Conclusion: This review of systematic reviews suggests that, although clear aligners may promote better oral hygiene and a temporary decrease in periodontal inflammation compared to fixed appliances, the differences are not clinically significant in the long term. Periodontal indices indicate a slight improvement in CAT compared to FAT. However, these advantages tend to diminish as the treatment progresses. Regarding the oral microbiota, both treatments may cause transient changes; however, no significant modifications are observed that could decisively influence overall periodontal health.